1990
DOI: 10.1203/00006450-199002000-00012
|View full text |Cite
|
Sign up to set email alerts
|

The Biphasic Effect of Amrinone on Tension Development in Newborn Mammalian Myocardium

Abstract: ABSTRACT. The effect of the bipyridine compound, amrinone, on tension generation in neonatal and adult myocardium was studied over the concentration range 30-500 pglmL. Increasing concentrations of amrinone caused a monotonic increase in twitch tension and the rate of tension development in adult papillary muscles. In contrast, lower concentrations of amrinone (30 and 100 pg/mL) caused a decrease in twitch tension and dP/dt in newborn papillary muscles, whereas 500 pg/mL amrinone caused a significant increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Myocardium from NB animals is relatively insensitive to this class of agents (14)(15)(16)(17), consistent with our observation of diminished cGMP-inhibited class I11 PDE activity in NB SR (12). Unlike that in AD rabbits, highaffinity cAMP PDE activity in the cytosolic fraction from NB myocardium is predominantly the class IV, cGMP-insensitive, cardiotonic drug-insensitive form (12).…”
supporting
confidence: 78%
See 2 more Smart Citations
“…Myocardium from NB animals is relatively insensitive to this class of agents (14)(15)(16)(17), consistent with our observation of diminished cGMP-inhibited class I11 PDE activity in NB SR (12). Unlike that in AD rabbits, highaffinity cAMP PDE activity in the cytosolic fraction from NB myocardium is predominantly the class IV, cGMP-insensitive, cardiotonic drug-insensitive form (12).…”
supporting
confidence: 78%
“…However, the effects of DMSO at concentrations near drug IC50 values were negligible (basal activity inhibited by less than 5%). of milrinone, a selective inhibitor of cGMP-inhibited class I11 Figure 1 illustrates the inotropic responses in papillary muscles PDE in the SR (14)(15)(16)(17). We attributed this lack of response in each age group increasing Ro NB rabbits to a relative deficiency of SR-associated class 111 PDE 20-1724' In the NB group, loo pM Ro 20-1724 reduced dT/dt activity (12).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In human neonates, cAMP-dependent inotropic agents are known to be less effective than in adults (38). Additionally, positive inotropic effects of phosphodiesterase inhibitors, such as milrinone or amrinone, are less pronounced or even inverted in newborn compared to adult animals (20,34). Therefore, substances with a cAMP-independent mode of action may be useful in the treatment of cardiac failure in neonates.…”
Section: Introductionmentioning
confidence: 99%
“…The difference in inotropic effect between milrinone and amrinone is in agreement with the results of Binah et al [5], who also found that these agents produced opposite inotropic effects on ventricular papillary muscles from neonatal dogs. Recently, Klitzner et al suggested that the negative inotropic effect of amrinone in neonatal hearts may result from a reduction in action potential duration (thus decreasing calcium influx), rather than an alteration of calcium regulation [28]. To our knowledge, the influence of milrinone on the action potential duration in the neonatal heart has not been examined.…”
Section: Discussionmentioning
confidence: 84%